House prices and household credit in the Eurozone: A single monetary policy with dissonant transmission mechanisms - Snyder, T.; Vale, S. (The Quarterly Review of Economics and Finance, 2022)
Booms and busts in house prices and household credit highlighted by the recent economic financial crisis, encourage a discussion on how the channels of monetary policy work. This paper studies the role of house prices and household credit in the transmission mechanism of the ECB monetary policy focusing on a panel of 12 Eurozone countries between 2000.Q1 and 2019.Q4. Considering the heterogeneity that characterized the Eurozone housing markets, the analysis distinguishes two groups of countries defined by their average growth of house prices, besides isolating the period that follows 2008.Q3 to capture the impact of the economic crisis. Using panel vector auto-regression models, the estimations indicate nominal money having an asymmetric impact across the Eurozone, being better adjusted to member countries with lower growth rates of house prices. For the whole period, house prices are more effective than credit as a monetary policy transmission channel to output fluctuations. However, the channels of monetary policy altered after the crisis, switching from a strong housing channel to a strong credit channel, especially for countries that experienced lower increase in house prices.